Applying analytic hierarchy process to the evaluation of double skin facades - Önder, Naime; BOSTANCIOĞLU, ESRA (My University, 2019)
A double skin facade (DSF) mediates the interaction between the outdoor environment and internal space, while also providing architectural flexibility to the building design. Designers and builders should evaluate DSF alternatives before selection of a design solution for a specific project context. In this study, Analytic Hierarchy Process (AHP) was used to evaluate questionnaire responses from experienced professionals. DSF alternatives and evaluation criteria were identified from the literature review and the hierarchical structure was determined based on the alternatives and the evaluation criteria. The evaluation criteria were used to measure and evaluate DSF. Experienced professionals evaluated criteria and DSF alternatives. The findings of this study provide designers and builders with valuable insights into DSF evaluation factors and DSF alternatives. The results may help designers and builders with the selection of facade systems.
Keywords: Double-skin Facade (DSF); Analytic Hierarchy Process (AHP); Multi-storey DSF; Corridor DSF; Shaft Box DSF; Box Window DSF